2013
DOI: 10.12776/ams.v19i4.181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Geometry and Cooling Rate on Properties of Sinter-Hardened Steels

Abstract: The aim of this paper is to deepen the understanding of the influence of the cooling step on the final properties of sinter-hardened components, mainly focusing on part geometry (through the definition of an A/M ratio) and cooling rate. A commercial Distaloy DH powder has been uniaxially pressed in different shapes, identified in terms of area/mass index, at three different compacting pressures (500, 600 and 800 MPa). During the sinter-hardening process, conducted in a belt-furnace, temperature profiles and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…As the temperature increases, Mn vapor reacts with oxygen and water vapor. Formed oxides are accumulated in residual pores, in accordance with other authors [1,6,9,11,28]. Salak [15] suggested that to utilize to the maximum extent the effect of sublimation and condensation of manganese vapors as a primary alloying mechanism, iron compacts must have mainly open pores, at least at the start of sintering, this ensures that by filling these pores the manganese vapors can affect the surface of all particles.…”
Section: Microstructure Developmentssupporting
confidence: 75%
See 1 more Smart Citation
“…As the temperature increases, Mn vapor reacts with oxygen and water vapor. Formed oxides are accumulated in residual pores, in accordance with other authors [1,6,9,11,28]. Salak [15] suggested that to utilize to the maximum extent the effect of sublimation and condensation of manganese vapors as a primary alloying mechanism, iron compacts must have mainly open pores, at least at the start of sintering, this ensures that by filling these pores the manganese vapors can affect the surface of all particles.…”
Section: Microstructure Developmentssupporting
confidence: 75%
“…During the past decade huge expansion [1][2][3][4][5][6][7][8][9][10][11] in manganese sintered steels research is evident, where manganese additions have been tried in various forms, starting from elemental blended addition of various grades of ferromanganese and master-alloy powders up to fully pre-alloyed powder. However, its industrial utilization is still very limited [12,13] as sintering of admixed combinations leads to high risk of oxidation during heating stage and the high vapor pressure can result in significant loss of manganese even during the heating up phase [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the presented microstructures are heterogeneous and depend on local atmosphere conditions, which are in good agreement with previous studies. 4,5,7,8,11,[15][16][17]19,20,23,24,[27][28][29]31,[34][35][36][37] 13b Wear tracks morphology for alloy A sintered in industrial atmosphere with detrimental effect of intensive plastic deformation in soft structure regions 14 Area of first sites of crack initiation and local damage in vacuum sintered steel B…”
Section: Discussionmentioning
confidence: 99%
“…In general, the presented microstructures are heterogeneous and depend on local atmosphere conditions, which are in good agreement with previous studies. 4,5,7,8,11,1517,19,20,23,24,2729,31,3437…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation